In vitro Antioxidant and in vivo Wound Healing Activities of the 80% Methanol Extract and Solvent Fractions of Seeds of Brassica carinata A. Braun (Brassicaceae) in Mice - Alemu BK; Ayalew Getahun K; Kahaliw W (Dove Medical Press, 2020)
Belete Kassa Alemu,1 Kefyalew Ayalew Getahun,2 Wubayehu Kahaliw2 1Department of Pharmacy, College of Medicine and Health Sciences, Wollo University, Dessie 1145, Ethiopia; 2Department of Pharmacology, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Belete Kassa AlemuDepartment of Pharmacy, College of Medicine and Health Sciences, Wollo University, P O Box; 1145, Dessie, EthiopiaTel +251 918330307Fax +251 333115052Email beletekassa0@gmail.comBackground: Brassica carinata is one of the traditional medicinal plants used in Ethiopia for the treatment of wounds and other diseases. However, the plant has not been scientifically validated, and thus the present study evaluated the in vitro anti-oxidant and the in vivo wound healing activity of the crude extract and solvent fractions of B. carinata seeds in mice.Materials and Methods: The crude extract was prepared by maceration using 80% methanol and formulated as 5% and 10% w/w ointments for topical application. The acute dermal toxicity was performed in female albino rats based on Organization for Economic Cooperation and Development (OECD) guideline number 434. Excision and incision wound healing models were used to evaluate the wound healing activities of crude extract and solvent fractions ointments in mice. Wound healing parameters such as wound area contraction and the period of epithelialization were determined in an excision model, whereas tensile strength was determined in an incision model. Moreover, the crude extract and solvent fractions were evaluated for the free radical scavenging activities in DPPH assay.Results: The acute dermal toxicity test showed that a limit dose of 2,000 mg/kg of 10% w/w crude extract ointment did not cause dermal toxicity in mice. In the excision wound model, the data revealed that 10% w/w ointment exhibited a significant wound contraction (from day 6 to 16, P< 0.001) effect with a significant decrease in epithelization period (at day 14, P< 0.001). In addition, 5% ointment of the crude extract showed a significant effect in wound contraction (from day 8 onwards, P< 0.01) and epithelization period (at day 16, P< 0.01). Despite all fractions being shown to promote wound healing, 10% w/w aqueous and ethyl acetate fractions showed a significant wound contraction (P< 0.001) effect starting from the 4th day onwards. Besides, the maximum antioxidant activity was seen in the aqueous fraction with an IC50 value of 3.45± 0.12 mg/mL.Conclusion: The present study demonstrated that the 80% methanol extract and solvent fractions of the seeds of B.carinata possess potential wound healing and anti-oxidant effects, supporting the traditional use of the plant for wound management.Keywords: wound, epithelialization, tensile strength, incision, excision, B. carinata, antioxidant